2017
DOI: 10.18052/www.scipress.com/ijet.10.11
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Mild Steel Corrosion in Sulphuric Acid Environment Using Wheat Starch

Abstract: The corrosion of mild steel in 0.5 M H2SO4acid solution and the inhibition process by wheat starch (WS) was investigated using weight loss and potentiodynamic polarization measurement techniques respectively. Gravimetric results revealed that there is significant reduction in the corrosion rate of mild steel in the presence of inhibited solution compared to blank solution, and also the inhibition efficiency was found to depend on the concentration of the WS. Data on potentiodynamic polarization results confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
(41 reference statements)
0
8
0
Order By: Relevance
“…To establish a complete, effective, and compact protective film, a suitable molybdate concentration is required. The efficiency of inhibitor in safeguarding or protecting metal surfaces during acid-induced corrosion is dependent on the ability of the molecular inhibitive species of the inhibitor to be adsorbed on the metal surface and the ability of the resulting adsorbed film to disengage the metal surface from the aggressive medium 29 .…”
Section: Potentiodynamic Polarization Studiesmentioning
confidence: 99%
“…To establish a complete, effective, and compact protective film, a suitable molybdate concentration is required. The efficiency of inhibitor in safeguarding or protecting metal surfaces during acid-induced corrosion is dependent on the ability of the molecular inhibitive species of the inhibitor to be adsorbed on the metal surface and the ability of the resulting adsorbed film to disengage the metal surface from the aggressive medium 29 .…”
Section: Potentiodynamic Polarization Studiesmentioning
confidence: 99%
“…The adsorption isotherms (regression models) were used to study the inhibition adsorption process, that is, to determine the mode of inhibition adsorption for the corrosion reaction process. Also, it was done to present the importance of using regression models and its methodology in interpreting corrosion inhibition results [16][17][18][19]. Regression isotherm models used in the research include; Temkin, Freundlich and Langmuir adsorption isotherm.…”
Section: Regression Analysis (Adsorption Isotherms)mentioning
confidence: 99%
“…The efficacy of inhibitor in safeguarding or protecting metal surfaces during acid induced corrosion is dependent on the ability of the molecular inhibitive species of the inhibitor to be adsorbed on the metal surface and the ability of the resulting adsorbed film to disengage the metal surface from the corrodent medium [17]. If it is believed that in inhibited solution corrosion occurs on the remaining free surfaces after some sites have been barricaded effectively by the adsorbed inhibitor film such that the covered surfaces have negligible rates of corrosion, the degree of surface coverage (θ) and inhibition efficiency (%I) can be computed according to the following Eqs.…”
Section: Inhibition Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, studies on corrosion inhibition performance of polymers have shown that some polymers are quite useful in retarding the corrosion of metal surface in aggressive environments. Typical examples of the polymers that have been utilized as corrosion inhibitors for metal in various aggressive media include starch [8][9][10], carboxymethyl cellulose [11,12], chitosan [13], gum arabic [14] water-soluble polymers [15], a blend of polyvinylpyrrolidone and polyacrylamide [16], etc. Despite the significant contributions of some polymers as corrosion inhibitors for metals in various aggressive media, it is worthy to note that acid metal corrosion still exists and the effectiveness and durability of polymeric inhibitors vary with metals, corrodents, the condition of corrosion environment, etc.…”
Section: Introductionmentioning
confidence: 99%